2023
DOI: 10.1002/1873-3468.14610
|View full text |Cite
|
Sign up to set email alerts
|

An NMR portrait of functional and dysfunctional allosteric cooperativity in cAMP‐dependent protein kinase A

Abstract: The cAMP‐dependent protein kinase A (PKA) is the archetypical eukaryotic kinase. The catalytic subunit (PKA‐C) structure is highly conserved among the AGC‐kinase family. PKA‐C is a bilobal enzyme with a dynamic N‐lobe, harbouring the Adenosine‐5′‐triphosphate (ATP) binding site and a more rigid helical C‐lobe. The substrate‐binding groove resides at the interface of the two lobes. A distinct feature of PKA‐C is the positive binding cooperativity between nucleotide and substrate. Several PKA‐C mutations lead to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 108 publications
0
6
0
Order By: Relevance
“…It appears that Tyr34 might have a swinging motion in solution, which is not observed in X-ray structures due to crystal packing limitations (Figure ). The NMR dynamics data reveal motions in DHP that are not evident in X-ray structures, as observed in other proteins, such as the flap dynamics observed in HIV-1 protease and the allosteric cooperativity network in the catalytic subunit of protein kinase A. …”
Section: Discussionmentioning
confidence: 91%
“…It appears that Tyr34 might have a swinging motion in solution, which is not observed in X-ray structures due to crystal packing limitations (Figure ). The NMR dynamics data reveal motions in DHP that are not evident in X-ray structures, as observed in other proteins, such as the flap dynamics observed in HIV-1 protease and the allosteric cooperativity network in the catalytic subunit of protein kinase A. …”
Section: Discussionmentioning
confidence: 91%
“…The importance of the C-4 loop was actually initially hinted at by computational analyses that involved Markov State modeling and NMR-restrained replica-averaged metadynamics (RAM). These analyses suggested that there may be a flip of the C-4 loop in the apo protein and in the mutant (62). As seen in In contrast, V104, which is part of the C-b4 loop, is one of three shell residues (SH1, SH2, and SH3) that flank the R-spine residues in the N-lobe and V104 also touches ATP (25).…”
Section: Synergistic High Affinity Binding Of Atp and Pseudo-substrat...mentioning
confidence: 94%
“…Adjacent residues in the C-4 loop (V104I, L103F/I, and P101A) are actually oncogenic mutations in several protein kinases, including PKA although none of these have been validated. The synergistic binding of ATP and IP20 was completely abolished for the F100A mutant; even though the Kms for Kemptide and ATP for the F100A mutant were similar to the wild type (wt) C-subunit (62). Peptide assays are a good way to evaluate the kinetic machinery of a protein kinase, and biochemically, based on the Kemptide peptide assay, the kinetic mechanism for the C-subunit was not altered significantly by the F100A mutation.…”
mentioning
confidence: 99%
“…NMR spectroscopy can provide valuable information about protein dynamics, interactions, and structural changes. NMR experiments on SHP2 mutants can characterize the effects of allosteric mutations on protein conformation and dynamics (Olivieri et al, 2023).…”
Section: Discovery Of Shp2 Allosteric Inhibitorsmentioning
confidence: 99%
“…NMR spectroscopy can provide valuable information about protein dynamics, interactions, and structural changes. NMR experiments on SHP2 mutants can characterize the effects of allosteric mutations on protein conformation and dynamics(Olivieri et al, 2023).Based on the identification of allosteric binding pockets and an understanding of the conformational landscape of SHP2 mutations, computational techniques, and biophysical methods can be used to discover new allosteric inhibitors. Virtual screening, structure-based drug design, and fragment-based drug discovery approaches can identify small molecules or compounds that can modulate the activity of mutated proteins and serve as potential allosteric inhibitors.…”
mentioning
confidence: 99%